Model Struktural Kepercayaan Masyarakat Pada Kebijakan Vaksinasi COVID-19 di Kota Jambi - Cut Multahadah (JURNAL GAMMA-PI, 2022)
Structural Equation Modeling (SEM) is a statistical method in multivariate analysis to test a theory or a hypothesis between variables in the form of relationships and not language. Structural Model in SEM describes the relationship between latent variables. Latent variables in SEM modeling function as exogenous variables or endogenous variables. In preventive health behavior on a person's belief to take disease action there is a late variable. Therefore, to analyze the trust of the Jambi city community towards the Covid-19 vaccination program policy, the SEM method was applied. Based on the results of the study, it can be said that the model of the structure of public trust in the COVID-19 vaccination policy in Jambi City is =1.15η+0.97ξ_1+0.99ξ_2+0.01. In general, the model can be accepted based on the GFI (Goodness of Fit Index) value of 0.908 and the AGFI (Adjusted Goodness of Fit Index) value of 0.859 which is close to 1.